2012
DOI: 10.1208/s12248-012-9341-x
|View full text |Cite
|
Sign up to set email alerts
|

Acarbose Bioequivalence: Exploration of New Pharmacodynamic Parameters

Abstract: Abstract. To investigate bioequivalence (BE) testing of an acarbose formulation in healthy Chinese volunteers through the use of recommended and innovative pharmacodynamic (PD) parameters. Following the Food and Drug Administration (FDA) guidance, a randomized, cross-over study of acarbose test (T) and reference (R) (Glucobay®) formulations was performed with a 1-week wash-out period. Preliminary pilot studies showed that the appropriate dose of acarbose was 2×50 mg, and the required number of subjects was 40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 3 publications
2
40
1
Order By: Relevance
“…In fact, the findings of several recent acarbose BE studies [7][8][9][10][11] performed in different countries indicated challenges in applying the current FDA-recommended BE evaluation method, and some researchers attempted to explore and propose new PD metrics, such as PD metrics reflecting the fluctuation of blood glucose. 7 However, all the PD metric exploration was based on the assumption that the reference and test formulations were bioequivalent, while in fact the premise was uncertain, so the applicability, sensitivity and scientificity of these new PD metrics still need further confirmation. Considering these limitations, our research was the first to determine the appropriateness of the FDA's guidance for assessing acarbose BE using branded drugs and to apply a more systematic assessment method to explore optimal indicating insufficient sensitivity of these PD metrics (Tables S1 and S2, Figure S3).…”
Section: The Applicability and Sensitivity Of Pd Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the findings of several recent acarbose BE studies [7][8][9][10][11] performed in different countries indicated challenges in applying the current FDA-recommended BE evaluation method, and some researchers attempted to explore and propose new PD metrics, such as PD metrics reflecting the fluctuation of blood glucose. 7 However, all the PD metric exploration was based on the assumption that the reference and test formulations were bioequivalent, while in fact the premise was uncertain, so the applicability, sensitivity and scientificity of these new PD metrics still need further confirmation. Considering these limitations, our research was the first to determine the appropriateness of the FDA's guidance for assessing acarbose BE using branded drugs and to apply a more systematic assessment method to explore optimal indicating insufficient sensitivity of these PD metrics (Tables S1 and S2, Figure S3).…”
Section: The Applicability and Sensitivity Of Pd Metricsmentioning
confidence: 99%
“…Thus far, owing to the importance of the FDA's guidance in drug research and development, multiple countries have carried out acarbose BE studies with reference to these guidelines. [7][8][9][10][11] However, both of these parameters are unsuitable for BE testing mainly because of the negative values of ΔAUC 0-4h and ΔC max0-4h during data processing, and the proportion of negative values can reach up to 30%. To guide BE studies, several new PD metrics have been proposed by different groups, [7][8][9][10][11] but the applicability, sensitivity and scientificity of these new PD metrics still need further confirmation because the effects of the formulation on acarbose BE cannot be ruled out.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two studies of generic acarbose in Asian countries compared locally available generic versions with the brand name. Both were bioequivalence studies, although one found irregularities within the limits allowed by the Korean drug regulatory authority [38,39].…”
Section: Studies Of Non-fda-approved Generic Versionsmentioning
confidence: 99%
“…Recently, a set of new bioequivalence criteria have been investigated in healthy Chinese volunteers by following the FDA recommended study design (Zhang et al 2012). In this study, consistent with the FDA guidance, serum glucose concentration was used as PD endpoint.…”
Section: Acarbose Tabletmentioning
confidence: 99%